Synergistic effects of mining and urban effluents on the level and distribution of methylmercury in a shallow aquatic ecosystem of the Bolivian Altiplano. Issue 12 (23rd November 2016) - Alanoca, L.; Guédron, S.; Amouroux, D.; Audry, S.; Monperrus, M.; Tessier, E.; Goix, S.; Acha, D.; Seyler, P.; Point, D.
Abstract : Lake Uru Uru (3686 m a.s.l.) located in the Bolivian Altiplano region receives both mining effluents and urban wastewater discharges originating from the surrounding local cities which are under rapid development. Abstract : Lake Uru Uru (3686 m a.s.l.) located in the Bolivian Altiplano region receives both mining effluents and urban wastewater discharges originating from the surrounding local cities which are under rapid development. We followed the spatiotemporal distribution of different mercury (Hg) compounds and other metal(oid)s ( e.g., Fe, Mn, Sb, Ti and W) in both water and sediments during the wet and dry seasons along a north-south transect of this shallow lake system. Along the transect, the highest Hg and metal(oid) concentrations in both water and sediments were found downstream of the confluences with mining effluents. Although a dilution effect was found for major elements during the wet season, mean Hg and metal(oid) concentrations did not significantly differ from the dry season due to the increase in acid mine drainage (AMD) inputs into the lake from upstream mining areas. In particular, high filtered (<0.45 μm) mono-methylmercury (MMHg) concentrations (0.69 ± 0.47 ng L −1 ) were measured in surface water representing 49 ± 11% of the total filtered Hg concentrations (THgF) for both seasons. Enhanced MMHg lability in relation with the water alkalinity, coupled with abundant organic ligands and colloids (especially for downstream mining effluents), are likely factors favoring Hg methylation and MMHg preservation while inhibiting MMHg photodegradation. Lake sediments were identified as the major source of MMHg for the shallow water column. During the dry season, diffusive fluxes were estimated to be 227 ng m −2 d −1 for MMHg. This contribution was found to be negligible during the wet season due to a probable shift of the redox front downwards in the sediments. During the wet season, the results obtained suggest that various sources such as mining effluents and benthic or macrophytic biofilms significantly contribute to MMHg inputs in the water column. This work demonstrates the seasonally dependent synergistic effect of AMD and urban effluents on the shallow, productive and evaporative high altitude lake ecosystems which promotes the formation of natural organometallic toxins such as MMHg in the water column.